Understanding the determinants of vaccine hesitancy and vaccine confidence among adolescents: a systematic review - Chiara Cadeddu; Carolina Castagna; Martina Sapienza; Teresa Eleonora Lanza; Rosaria Messina; Manuela Chiavarini; Walter Ricciardi; Chiara de Waure (Taylor & Francis Group, 2021)
Vaccine hesitancy (VH) in the age of adolescence is a major public health issue, though it has not been widely examined in the scientific literature. This systematic review aims to address the determinants of VH among adolescents aged 10-19. PubMed, Scopus, and Web of Science were searched from the inception until 11 December 2020. Articles in English, assessing adolescents' attitudes toward vaccination in terms of hesitancy and/or confidence were considered eligible. Out of 14,704 articles, 20 studies were included in the qualitative analysis. Quality assessment was performed through the Appraisal tool for Cross-Sectional Studies (AXIS). A better knowledge of vaccine-preventable diseases, a higher confidence in vaccines, as well as an active involvement in the decision-making process showed a positive relationship with adolescents' vaccine uptake. These aspects should be considered to plan tailored interventions for the promotion of vaccination among adolescents and to reduce VH. Major limitations of this review are represented by the high heterogeneity of the tools used in the primary studies and the lack of standardization in outcomes definitions. Future research is needed to disentangle the interrelationship among the different determinants of VH in this age group.